2018
DOI: 10.4314/ajoh.v7i2.172403
|View full text |Cite
|
Sign up to set email alerts
|

A report on oral health delivery to rural underserved communities oyo state using the mobile dental clinic

Abstract: A report on oral health delivery to rural underserved communities oyo state using the mobile dental clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The mean clinical attachment loss was worse with the increasing age of respondents, which some studies have reportedly claimed to be due to increased susceptibility of periodontal tissue with increasing age (Table 2) [17] [18]. However, other studies have reported that the increased attachment loss seen with the increasing age could be due to the individual host susceptibility to periodontal disease rather than the length of time the plaque is present (age effect) [23]. The greater the age of an individual, the slower the rate of wound healing and this increases susceptibility to periodontal disease [24].…”
Section: Discussionmentioning
confidence: 99%
“…The mean clinical attachment loss was worse with the increasing age of respondents, which some studies have reportedly claimed to be due to increased susceptibility of periodontal tissue with increasing age (Table 2) [17] [18]. However, other studies have reported that the increased attachment loss seen with the increasing age could be due to the individual host susceptibility to periodontal disease rather than the length of time the plaque is present (age effect) [23]. The greater the age of an individual, the slower the rate of wound healing and this increases susceptibility to periodontal disease [24].…”
Section: Discussionmentioning
confidence: 99%